Síntese e caracterização elétrica do eletrólito sólido Ba5Nb4O15 para utilização em células a combustível - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
An alternative to reducing the operating temperature of solid oxide fuel cells (SOFC) is the use of proton conductive electrolytes. Thus, this work evaluated the viability of the compound Ba5Nb4O15 (BNO) as a possible electrolyte candidate for SOFC, which has a structure of hexagonal perovskite and possibility of proton conductivity. For this, the sinterability of barium niobate was compared by densification after being synthesized via solid state reaction, pressed and sintered at two temperatures: 1250 and 1450 ºC. In addition, the influence of the addition of lower valence dopants (titanium and zirconium) on the structure and electrical properties of the pure phase was analyzed. The samples were characterized by X-ray diffraction, scanning electron microscopy and impedance spectroscopy. The electrical measurements were performed in the range of 350 ºC to 550 ºC, in atmosphere of dry air and humid air. In general, the best sintering temperature for obtaining the pure BNO phase is 1250 °C, due to the desintering process, where above that temperature there is no more densification. The activation energy obtained and the conductivities were: 0.78 eV and 2,03x10-6 S.cm-1 (BNO); 0.48 eV and 7,81x10-6 S.cm-1 (0.3 mol% of Ti); and 0.76 eV and 8,71x10-6 S.cm-1 (0.5 mol% of Zr). Although the samples did not densify sufficiently the results corrected by Archie's law showed that BNO doping improves its electrical properties.
Keywords: Condutividade protônica; Perovisquitas hexagonais; Niobato de bário; Protonic conduction; Hexagonal perovskites; Barium niobate; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA